2006
DOI: 10.1182/blood-2005-08-3329
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into the role of Notch signaling in tumorigenesis

Abstract: Members of the Notch family of transmembrane receptors play an important role in cell fate determination. Over the past decade, a role for Notch in the pathogenesis of hematologic and solid malignancies has become apparent. Numerous cellular functions and microenvironmental cues associated with tumorigenesis are modulated by Notch signaling, including proliferation, apoptosis, adhesion, epithelial-to-mesenchymal transition, and angiogenesis. It is becoming increasingly evident that Notch signaling can be both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
428
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(437 citation statements)
references
References 141 publications
6
428
1
2
Order By: Relevance
“…Some studies have suggested that in some cancers increased Notch gene copy number can correlate with increased Notch signaling (Bray, 2006;Leong and Karsan, 2006;Park et al, 2006). In our study, although we noted that the Notch 2 locus (1p13-11) in Mary-X was moderately amplified on array comparative genomic hybridization, the Notch 3 locus was not amplified.…”
Section: Notch 3 Dependency Of Ibc Embolus Y Xiao Et Alcontrasting
confidence: 60%
See 2 more Smart Citations
“…Some studies have suggested that in some cancers increased Notch gene copy number can correlate with increased Notch signaling (Bray, 2006;Leong and Karsan, 2006;Park et al, 2006). In our study, although we noted that the Notch 2 locus (1p13-11) in Mary-X was moderately amplified on array comparative genomic hybridization, the Notch 3 locus was not amplified.…”
Section: Notch 3 Dependency Of Ibc Embolus Y Xiao Et Alcontrasting
confidence: 60%
“…Notch, especially Notch 1, has been shown to signal in a number of different human breast cancer cell lines and to induce EMT through slug-mediated repression of E-cadherin (Stylianou et al, 2006;Leong et al, 2007). Some studies have revealed, however, that Notch was not sufficient for transformation when it was activated alone (Ayyanan et al, 2006) but needed to synergize with additional molecular alterations to promote neoplastic transformation (Leong and Karsan, 2006). The cross-talk between Notch and other oncogenetic signaling pathways could then form a feed-forward loop that promoted tumor cell growth (Girard et al, 1996;Palomero et al, 2006).…”
Section: Notch 3 Dependency Of Ibc Embolus Y Xiao Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…However, aberrant activation of the Notch pathway has also been shown to be involved in tumorigenesis and the development of EMT in several cancer types. 16 After extracellular activation by Jagged/Dll, the transmembrane protein Notch is cleaved by c-secretase, and the released intracellular domain of Notch (NICD) activates related transcription factors 9 and sets the fate of the cell to enter the EMT. Notch signaling enhances primary melanoma metastasis through effects on b-catenin signaling.…”
mentioning
confidence: 99%
“…It regulates multiple steps of T and B cell development, T cell activation, regulatory T-cell function and T-helper cell differentiation [7][8][9][10][11]. Furthermore, it helps in the development and differentiation of many other hematopoietic and immune cells [12]. Deregulation of Notch signalling has been linked to multiple human diseases especially T-acute lymphocytic leukemia [13,14] and recently, it has been related to the development of many autoimmune disorders as ITP [15].…”
Section: Introductionmentioning
confidence: 99%